MENELAAH SAFAR DALAM PSIKOLOGI ISLAM - Subhan Subhan (Jurnal An-Nufus, 2020)
This article discusses the concept of safar in the perspective of Islamic psychology which has not been widely studied scientifically. Safar is usually more interpreted as a mere physical journey, without any attempt to cultivate psychological values cum spiritual. For this reason, the author explores safar based on the sufi point of view of Imam Al-Ghazali. The method in this research uses two approaches: literature study written by Imam al-Ghazali and empirical data mining by interviewing doctoral students of Islamic psychology study program at Muhammadiyah University of Yogyakarta. Some of the findings in this research include: safar is very beneficial for the psyche of a person who is a traveler, even when the traveler is experiencing obstacles in his safar.